Why RE's radical reform could fail: The politics of epistemology and the economics of producer capture. Issue 3 (3rd July 2022) - Chater, Mark
ABSTRACT: This article, which is developed from a keynote given to the Humanists UK RE conference on 28 November 2020 draws attention to the interest groups that operate in and around the world of professional religious education (RE) in England. It argues that reform of RE could still fail. Two factors could spell its end. First is the politics of epistemology, the embedded power structures that shape knowledge and curriculum in the subject. Second is the economics of producer capture, which takes up critical questions about how the RE world is structured, organised, and funded, and how its stakeholders' interests operate. My definition and exploration of these two factors is followed by a description of how they apply in the RE community. I conclude by urging the RE professional community to face these issues and create new structures which more appropriately serve schools and children.